The bidirectional association between depression and sarcopenia: a systematic review and meta-analysis - Zhu, Yuan; Pan, Mengjia; Qiu, Yu; An, Zhenmei; Li, Shuangqing (Frontiers in Public Health, 2025)
BackgroundSarcopenia, a geriatric syndrome characterized by progressive loss of muscle mass, strength, and physical performance, elevates risks of functional decline and mortality. This study aims to investigate the co-occurrence patterns between depression and sarcopenia and characterize their epidemiological linkages.MethodsWe systematically searched PubMed, Embase, Scopus, and Web of Science for studies examining depression and sarcopenia (published by July 12, 2024). Our review encompasses literature on sarcopenia prevalence, its co-occurrence with depression, and the odds ratio (OR) between these conditions. We performed statistical analyses using R.ResultsAnalysis of 36 studies demonstrated significantly higher pooled depression prevalence among sarcopenic individuals (0.24; 95% CI: 0.18–0.30; I2 = 95.6%) compared to non-sarcopenic controls, with sarcopenia conferring increased depression likelihood (adjusted OR = 1.49; 95% CI: 1.23–1.81; I2 = 85.8%). Similar patterns emerged for possible sarcopenia (depression prevalence: 0.15; 95% CI: 0.11–0.19; I2 = 86.4%; adjusted OR = 1.42; 95% CI: 1.10–1.83; I2 = 79.4%). Conversely, while sarcopenia prevalence was elevated in depression cohorts (0.20; 95% CI: 0.02–0.38; I2 = 94.2%), the adjusted association was non-significant (OR = 1.87; 95% CI: 0.74–4.71; I2 = 78.5%).ConclusionSarcopenia is significantly associated with higher depression prevalence and increased depression likelihood. While sarcopenia prevalence is elevated in depression populations, their bidirectional association requires further investigation. Future research should focus on elucidating underlying mechanisms.Systematic review registrationThis review was registered with PROSPERO (number CRD42024572944).